Paths & portals - Yang, Gene Luen. (New York, NY : First Second, 2016)
In a secret underground classroom Hopper, Eni, and Josh discover that the campus was once home to the Bee School, an institute where teachers, students, and robots worked together to unravel the mysteries of coding. Hopper and her friends are eager to follow in this tradition and become top-rate coders. But why are Principal Dean and the rugby team suddenly so interested in their extracurricular activities?
GN430L
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Gifted children -- Comic books, strips, etc; Schools -- Comic books, strips, etc -- Fiction; Computer programming -- Comic books, strips, etc; Gifted children -- Fiction; Private schools -- Fiction; Computer programming -- Fiction; Science fiction; Graphic novels